Contribution analysis for adaptive management - Apgar, Marina; Hernandez, Kevin; Ton, Giel (Briefing Paper, 2020)
This briefing note shares practical learning on the use of contribution analysis for adaptive management (CA4AM). It examines how the approach enables programmes to work with theories of change in a practical, reflexive way, and how, combined with assessing evidence of a programme’s contribution to change, its findings can inform programme adaptation. It also examines both how and to what extent CA enables AM through the experiences of four large complex programmes all working towards systems-level change and employing a structured process of reflection on theories of change. Key messages CA4AM can enable programmes to work with theories of change in a practical, reflexive way. It is particularly useful for programmes operating in conditions of complexity, when it is difficult to discern attribution and when systems-level change is the goal. A range of enabling factors help CA4AM to be used most effectively, including contractual flexibility; embedded monitoring, evaluation and learning (MEL); and supportive leadership.

Supporting adaptive management. Monitoring and evaluation tools and approaches - Pasanen, Tiina; Barnett, Inka (ODI, 2019)
Key messages • This working paper introduces a set of monitoring and evaluation (M&E) tools and approaches, discussing their potential usefulness in supporting adaptive management in development and humanitarian programmes. It emphasises adaptive programmes characterised by complex aspects, such as: (1) they are innovative; (2) they have uncertain pathways for change; or (3) they operate in uncertain or unstable environments. • The majority of these tools have been used in international development for many years. However, adaptive management brings additional challenges for monitoring and evaluating programmes, as they require intentional M&E design from the start that is oriented towards both learning and accountability. • All of the tools and approaches introduced in this paper have potential to support learning and adaptation, although in various ways and at different stages of a programme. Some tools can support strategic planning and diagnosing throughout a programme – especially during design and inception – while others can help analyse causal relationships at specific points in a programme. It is important to tailor the approach used for its intended purpose. However, whether learning and adaptation happens depends also on factors other than the choice of M&E methods. • For some of these approaches a considerable body of evidence already exists but, for many, more practical examples and systematic analysis is needed. In addition to building the evidence base concerned with which approaches are suitable for different types of adaptive programmes and why, it is also important to improve understanding of the enabling environmental conditions necessary for the tools and approaches outlined here to facilitate and strengthen evaluative thinking, evidence-informed decision-making and ongoing programme iteration.

Learning and adapting: the use of monitoring and evaluation in countering violent extremism: a handbook for practitioners - Dawson, Laura; Edwards, Charlie; Jeffray, Calum; Royal United Services Institute for Defence and Security Studies (Royal United Services Institute for Defence and Security Studies, 2014)
IN 2013, the Royal United Services Institute for Defence and Security Studies (RUSI) was awarded a grant under the Kanishka Project to develop a handbook for monitoring and evaluating counter violent extremism (CVE) policies and programmes. The aim of this handbook is to support CVE policy-makers and practitioners (those who design, manage and evaluate CVE programmes), by providing them with key terms regarding violent extremism and radicalisation, describing the purpose of evaluation, and providing examples of key methodologies they can employ to conduct monitoring and evaluation (M&E) in this emerging policy field. The handbook will enable readers to understand why, when and how to conduct an evaluation of a CVE policy, programme or project. .

Examining the results and adaptation ideas in foreign aid - Janus, Heiner (University of Manchester, 2020)
This thesis applies ideational and institutional theories to analyse how two specific ideas, results and adaptation, have changed the theory and practice of development cooperation. The thesis addresses the question of why the results and adaptation ideas are often treated as binaries and how this debate has evolved historically. In a first theoretical paper, the evolution of results and adaptation is conceptualised as a combination of institutional layering and diffusion within development organisations. The second theoretical paper applies ideational theory, in particular, the coalition magnet framework, to China as a donor country. The empirical papers apply ideational and institutional theories to study aid projects funded by the World Bank and China in the Rwandan agriculture sector. The third paper analyses through which mechanism, results-based principal-agent relationships or problem-driven iterative adaptation, the World Bankâs Program for Results in the agriculture sector in Rwanda has led to increased agricultural productivity. The paper combines causal process tracing and contribution analysis to investigate two underlying theories of change of the Program for Results. The fourth paper applies the same framework and methodology to the Chinese Agricultural Technology Demonstration Center in Rwanda. The fifth paper compares both projects, the World Bank project and the Chinese project. The thesis finds that the ideas of results and adaptation are often presented as mutually exclusive mainly at the general level of public philosophies or paradigms, but show overlap and potential for integration on the level of framing policy problems and policy solutions. The thesis also demonstrates that there is unexplored potential for convergence between China and Development Assistance Committee donors around âcoalition magnetâ ideas. The empirical part of the thesis reveals how results-based and adaptive causal mechanisms co-exist within given aid interventions by the World Bank and China, how these interact and how they ultimately contribute to achieving development outcomes. The key finding is that the broader political context of the Rwandan agricultural sector is the main factor for determining development outcomes, which neither the World Bank project nor the Chinese projects take into account. The comparison of the World Bankâs and Chinaâs interventions finds that donor organisations need to address how results-based ideas in combination adaptive development ideas can be better tailored to fit into the specific context of the Rwandan agriculture sector.